Социологическая концепция гражданского общества в постсоветском контексте - Степаненко, В. (Социология: теория, методы, маркетинг, 2001)
The main issues of the construction of the civil society in the post-communist perspective are analyzed in the paper. “Civil society” is considered as a normative sociological concept and an actual practice of social transformation. Two basic models of the civil society project in post- communist countries and particularly in Ukraine are examined. The principal statement of the paper is the diagnosis of the democratic process in Ukraine, its main lack and shortages as connected with the confusion between concept and political practice of democratization and those of civil society. There is shown how the concept of civil society can be applied for understanding difficulties and perspectives of the reform process in Ukraine.